Fear of falls, physical performance and physical activity levels among older adults with falls and recurrent falls - Resshaya Roobini Murukesu,; Devinder Kaur Ajit Singh,; Tong, Pei Shan; Normala Mesbah,; Heaw, Yu Chi; Ng, Cheah Ping (Penerbit Universiti Kebangsaan Malaysia, 2019)
Older adults who fall recurrently have sub-optimal physical performance especially muscle strength, mobility and balance. Recurrent falls lead to a heightened fear of falls. However, there is limited information regarding other domains of physical performance, namely flexibility and endurance. In addition, there is still limited knowledge pertaining fear of falls and physical activity levels among Malaysian community-dwelling older adults who are recurrent fallers. The aim of our study was to compare fear of falls, physical performance and physical activity levels among older adults with falls and recurrent falls. This cross- sectional study was carried out in two Malaysian urban districts. Physical performance was examined using Functional Fitness MOT (FFMOT). Modified Baecke Questionnaire and Activities-Specific Balance Confidence (ABC-6) Scale were administered to evaluate the level of daily physical activity and fear of falls respectively. A total of 35 older adults participated in this study, 20 fallers (mean age: 71.95±8.22) and 15 recurrent fallers (mean age: 76.73±8.82) respectively. Our study results showed that older adults with recurrent falls had significantly reduced lower extremity strength, dynamic balance, endurance, balance confidence in activities of daily living and physical activity levels compared to faller group (p < 0.05). Although flexibility and upper limb strength were not significantly different among fallers and recurrent fallers, overall improvement in physical performance should be targetted in falls prevention and management. This is vital to prevent further deterioration in physical performance among older adults with recurrent falls.